IMPACT OF MATERNAL WEIGHT GAIN AND INFLAMMATORY MARKERS ON NEONATAL IRON DEFICIENCY: A CROSS-SECTIONAL STUDY FROM A PEDIATRIC PERSPECTIVE - Santosa, Qodri; Oliviany, Windy; Hafiidhaturrahmah, Hafiidhaturrahmah; Pratidina, Wening Gelar; Hapsari, Ariadne Tiara; Priyanto, Edy; Muntafiah, Alfi (Medical and Health Journal, 2025)
Background: Maternal health during pregnancy is crucial for neonatal outcomes, particularly regarding iron status. This study investigates the impact of maternal weight gain and inflammatory markers on neonatal iron deficiency in a cohort of mothers and their newborns. Methods: A cross-sectional study was conducted involving spontaneously delivered infants from single, full-term pregnancies, with Apgar scores ≥7 at the first minute and normal birth weights (≥2,500 to <4,000 grams). Maternal weight gain was categorized as "appropriate" or "inappropriate" based on the 2009 Institute of Medicine (IOM) recommendations. Maternal blood samples were collected during the third trimester, and infant iron status was assessed through hematological parameters and serum iron levels. Statistical analyses included the Mann-Whitney test and independent t-tests, with significance set at p < 0.05. Results: A total of 59.5% of mothers did not achieve appropriate weight gain, and 57.1% exhibited positive CRP levels, indicating inflammation. Infants born to mothers with appropriate weight gain had significantly better hematological parameters, including higher erythrocyte counts, hemoglobin, and hematocrit levels (p < 0.05). Conversely, infants of mothers with positive CRP levels demonstrated lower erythrocyte counts and hemoglobin levels, indicating a potential negative impact of maternal inflammation on iron transfer (p < 0.05). No significant differences in neonatal iron status were observed between infants born to anemic and non-anemic mothers. Discussion: The findings underscore the importance of monitoring maternal nutritional status and inflammatory markers during pregnancy. Adequate weight gain according to IOM guidelines is associated with improved neonatal iron status, while maternal inflammation negatively impacts iron transfer to the fetus. These results highlight the need for targeted interventions, including nutritional education and management of inflammatory conditions, to enhance maternal and neonatal health outcomes. Conclusion: This study contributes to the understanding of the relationships between maternal weight gain, inflammatory markers, and neonatal iron status. By addressing these factors, healthcare providers can improve outcomes for mothers and their newborns, ultimately promoting healthier populations.